Q-switched ytterbium-doped fiber laser with nickel oxide nanoparticles saturable absorber - Jannifar, A.; Baharom, Mohd Faizal; Zulkipli, N.F.; Jufriadi, -; Harun, Sulaiman Wadi (Old City Publishing, 2018)
We experimentally demonstrate a passively Q-switched Ytterbium-doped fiber laser (YDFL) operation by using a Nickel oxide (NiO) nanoparticles as a saturable absorber (SA). As a kind of transition metal oxide, the NiO has a large nonlinear optical response with a fast response time for SA. By embedding the synthesized NiO5 into a poly ethylene glycol (PEO) film and incorporating in a laser cavity, a Q-switching pulses train was successfully generated to operate at 1070 nm wavelength. A stable passively Q-switched EDFL pulses with maximum output pulse energy of 0.69 nJ, repetition rate of 54.35 kHz, and pulse width of 2.27 µs are achieved when the incident pump power is 226 mW. The results indicate NiO nanoparticles can work as a Q-switcher for operation at 1 micron region.